Endothelial progenitor and mesenchymal stromal cells in newborns with congenital diaphragmatic hernia undergoing extracorporeal membrane oxygenation - Rafat, Neysan; Patry, Christian; Sabet, Ursula; Viergutz, Tim; Weiß, Christel; Tönshoff, Burkhard; Beck, Grietje; Schaible, Thomas (Frontiers in Pediatrics, 2019)
Background: Endothelial progenitor (EPC) and mesenchymal stromal cells (MSC) can regenerate damaged endothelium and thereby improve pulmonary endothelial dysfunction. We do not know, how extracorporeal membrane oxygenation (ECMO) might affect EPC- and MSC-mediated regenerative pathways in patients with congenital diaphragmatic hernia (CDH). Therefore, we investigated, if ECMO support impacts EPC and MSC numbers in CDH patients. Methods: Peripheral blood mononuclear cells from newborns with ECMO-dependent (n=18) and ECMO-independent CDH (n=12) and from healthy controls (n=12) were isolated. The number of EPC and MSC was identified by flowcytometry. Serum levels of vascular endothelial growth factor (VEGF) and angiopoietin (Ang)-2 were determined. Results: EPC and MSC were elevated in newborns with CDH. ECMO-dependent infants had higher EPC subpopulation counts (2,1-7,6-fold) before treatment compared to ECMO-independent infants. In the disease course, EPC and MSC subpopulation counts in ECMO-dependent infants were lower than before ECMO initiation. During ECMO, VEGF serum levels were significantly reduced (by 90,5%) and Ang2 levels significantly increased (by 74,8%). Conclusions: Our data suggest that ECMO might be associated with a rather impaired mobilization of EPC and MSC and with a depression of VEGF serum levels in newborns with CDH.